Diversity of phytoplankton in coastal water of Kuantan,Pahang, Malaysia - Mohammad Noor, Normawaty; Harun, Siti Nor Rahaida; Mat Lazim, Zainab; Mukai, Yukinori; Mohamad, Najma Tasnim; Saad, Shahbudin (Universiti Malaya, 2013)
A study on diversity of phytoplankton was carried out in the coastal water of Kuantan, Pahang, Malaysia. Eighteen samples of seawater were collected from six stations from September 2011 to March 2012. This study was aimed to identify phytoplankton, to determine the species abundance and diversity. Physico-chemical parameters such as pH, salinity, temperature and dissolved oxygen were recorded. Based on light microscopy, 70 taxa composed of 63 species of diatoms and 7 species of dinoflagellates were identified. Bacteriastrum delicatulum, Chaetoceros spp., and Coscinodiscus spp., were found to be dominant almost at all stations. Some potential harmful species identified were Ceratium fusus, Prorocentrum micans and Chaetoceros sp. The highest cell density was 32 x 103 cells/L and the lowest was 7.9 x 103 cells/L at stations 3 and 5, respectively. Significantly high number of cell density was found during NEM compared to other monsoons.